Contribution of the historians of the Diaspora into the state tendency Ukrainian historiography - Розмериця Ю. (Київський національний університет імені Тараса Шевченка, 2007)
It is elucidated the role of Ukrainian Diaspora in formation of the state conception of Ukrainian Diaspora, its implementation in the Ukrainian high educational establishments on the territory of Czechoslovakia and Germany.

Висвітлено роль української діаспори у формуванні державницької концепції української історії, її реалізацію в українських вищих навчальних закладах на території Чехословаччини та Німеччини.
Внесок істориків діаспори в розвиток державницького напряму української історіографії